THE DILEMMA OF MERITS AND DRAWBACKS OF CODE-SWITCHING IN AN ELEMENTARY EFL CLASSROOM - Miftahul Mahrus; Lailiy Kurnia Ilahi; Novinda Rosayanti (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2026)
The dilemma of the merits and drawbacks of code-switching in an EFL classroom at the elementary school level in Indonesia becomes the subject of investigation in this study. This study employed a qualitative case study design. An English teacher from a public school was purposively selected as an information-rich case. Classroom observations, semi-structured interviews, and documentation were used to collect the data. The findings of this study reveal that the practice of code-switching can improve students’ comprehension, engagement, and initiative, and save time for classroom management. While acknowledging its merits, this study also points to several drawbacks, such as persistent code-switching reducing students’ exposure to English and leading them to rely on their first language. This can also pose problems in maintaining the balance between the two languages, indicating the dilemma for the teacher between providing immediate learning support and encouraging the development of students’ English language skills. Therefore, code-switching is suggested to be used selectively, especially for clarifying the subject needs while simultaneously striving to maintain the English input proportion. Additionally, future studies should explore the longitudinal impact of implementing code-switching in EFL classrooms on the students’ abilities.